2005
DOI: 10.1192/bjp.186.1.74
|View full text |Cite
|
Sign up to set email alerts
|

First-contact incidence of schizophrenia in Surinam

Abstract: SummaryWe tested the hypothesis that the increased incidence of schizophrenia among Surinamese immigrants to The Netherlands could be explained by a similarly high incidence in Surinam. We conducted a 1-year first-contact incidence study in Surinam and compared the findings with data from a similar study conducted in The Netherlands using the same inclusion criteria and instruments. The risk of developing a schizophrenic disorder was 2.4 times higher (95% CI 1.3–4.2) in Surinamese immigrants than in residents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 8 publications
1
34
0
Order By: Relevance
“…The incidence rates of schizophrenia in Jamaica, Trinidad, and Barbados were found to be more similar to the rate for the white population in the United Kingdom and were significantly lower than the comparable rate for the UK AfricanCaribbean population. Selten et al 27 further found that incidence rates in the Surinam were significantly lower than among Surinamese migrants to the Netherlands. The question of whether the raised rates can be explained as methodological artifact has been mentioned above.…”
Section: Is the Rate Of Schizophrenia Raised In The Country Of Origin?mentioning
confidence: 99%
“…The incidence rates of schizophrenia in Jamaica, Trinidad, and Barbados were found to be more similar to the rate for the white population in the United Kingdom and were significantly lower than the comparable rate for the UK AfricanCaribbean population. Selten et al 27 further found that incidence rates in the Surinam were significantly lower than among Surinamese migrants to the Netherlands. The question of whether the raised rates can be explained as methodological artifact has been mentioned above.…”
Section: Is the Rate Of Schizophrenia Raised In The Country Of Origin?mentioning
confidence: 99%
“…Notably, studies of the sending countries have found normal incidence rates of schizophrenia. [25][26][27] The unusually high risks for second-generation immigrants are striking, insofar as they cannot be attributed to the selective migration of persons who are already ill or in the prodromal phase, nor can they be attributed to genetics. [28][29] Viable explanations for the migrant effect must meet the challenge posed by the increased rates found in both first-and second-generation immigrants.…”
Section: Evidence From Migrant Studiesmentioning
confidence: 99%
“…By conducting research in the culture of origin of the immigrants, some authors tried to find out whether the original culture of the migrant groups could serve as an explanation for increased levels of problem behaviour in migrant youth in the host country. The assumption was that absence of an increased level of problem behaviour in the country of origin compared to scores of natives in the host culture would rule out this cultural explanation (see Mahy, Mallett, Leff, and Bhugra (1999) and Selten et al. (2005) for parallel studies on cultural explanations for schizophrenia in adult immigrants from Barbados and Surinam).…”
mentioning
confidence: 99%